The reformed tradition always reforming? : a historical-theological study of the doctrine of justification in the works of John Calvin, Jonathan Edwards and N.T. Wright - Huggins, Jonathan Ray (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.